Voces de pervivencia, el territorio de resguardo indígena en la Amazonia colombiana, apuesta colectiva para resistir a la violencia política: experiencia del Resguardo Indígena Panuré-Guaviare (1894-1998) - PLAZAS SIERRA, Andrés Mauricio (2017)
This work focuses on analyze the course of collective actions that allowed the constitution of indigenous territories in colombian Amazon, during a period of armed confrontation between 1984 and 1998. To delimitate the objective, it is based on the category of region to understand the process of definition of the department of Guaviare, and in the same scope the territory is detailed to identify the collective elaborations that led to the realization of the "Resguardo Indígena Panuré", a specific experience where historical reflections confluent. In this research the proposal is guided by the theoretical principles of the history of the present time, for this reason it will look for give relevance to the poorly documented collective activity of contemporary Amazonian indigenous communities, deepening the discussion about the effects of its articulation to the structure of the State as an organization, and in it, to follow up the neoliberal postulates of sustainable development for the region. Thus, is used the interpretation of oral sources, rescued in spaces of discussion of colombian indigenous organizations and in interviews, besides the interpretation of the effects of their territorial activities on the cartographic reproduction of the Amazon region.